Numerical Simulation Study on Parameter Optimization of Time Sequential Controlled Blasting. (23rd February 2022) - He, Meng; Hu, Yehong; Chen, Jin; Zhang, Jiazhao; Li, Helong; Cai, Changgeng
Abstract : In order to reduce the damage of blasting to rock mass and improve the half-hole rate of presplitting blasting, the dynamic finite element analysis software ANSYS/LS-DYNA is used to simulate and analyze the action process of sequential controlled blasting. The effects of the detonation delay time of the postblasting hole and the hole spacing of the postblasting hole on the crack formation of the sequential controlled presplitting blasting are studied. The results show that when the blast hole with a diameter of 42 mm is used for sequential controlled presplitting blasting and the first blast hole pitch is 60 cm, the reasonable detonation delay time is 80∼120  μ s. When the detonation delay time is 80  μ s, the reasonable postblast hole spacing is 60 cm. Field tests show that when reasonable optimized blasting parameters are used, presplit blasting with sequential control can reduce drilling workload and explosive consumption. The sequential controlled presplitting blasting not only increases the hole spacing but also plays a better role in protecting the surrounding rock.